Comparative Performance of SVM and BERT-Base Using Hybrid Preprocessing for Fast Fashion Sentiment Analysis - Mulianingrum, Restu Lestari; Hidayat , Erwin Yudi (Journal of Applied Informatics and Computing, 2025)
Fast fashion poses major environmental and social challenges, yet public awareness in Indonesia remains insufficiently understood. This study compares Support Vector Machine and BERT-Base for sentiment analysis of 3,513 TikTok comments on fast fashion sustainability using a hybrid preprocessing pipeline that incorporates a 404-entry slang dictionary and IndoNLP utilities to address informal language, code-mixing, and character elongation. Sentiment labels generated using VADER were validated against 1,747 manually annotated samples, achieving Cohen's Kappa of 0.7155, indicating substantial agreement. BERT-Base achieves 92.7% accuracy with F1-scores of 0.86, 0.94, and 0.93 for negative, neutral, and positive classes, while SVM attains competitive 90.4% accuracy with F1-scores of 0.84, 0.93, and 0.91. BERT demonstrates superior negative sentiment detection with recall of 0.87 compared to SVM at 0.82, critical for identifying sustainability concerns. Computational analysis reveals significant trade-offs as BERT requires 230.2 seconds of GPU training and 3.449 seconds of inference, whereas SVM operates efficiently on CPU with 25.9 seconds of training and 0.051 seconds of inference, representing 8.9× and 67.6× efficiency advantages. The sentiment distribution comprising 46.9% neutral, 34.5% positive, and 18.6% negative comments indicates limited critical awareness among Indonesian users. These findings demonstrate that systematic preprocessing bridges the performance gap between classical and transformer models while enabling deployment decisions based on resource constraints, providing methodological insights for low-resource informal text analysis and practical guidance for scalable social listening, greenwashing detection, and evidence-based sustainability communication strategies.